A genetic study of type 2 neurofibromatosis in the United Kingdom. I. Prevalence, mutation rate, fitness, and confirmation of maternal transmission effect on severity. Issue 12 (December 1992) - Evans, D G; Huson, S M; Donnai, D; Neary, W; Blair, V; Teare, D; Newton, V; Strachan, T; Ramsden, R; Harris, R
Abstract : A clinical and genetic study of type 2 neurofibromatosis (NF2) has been carried out in the United Kingdom. Virtually complete ascertainment of cases in the north-west of England was achieved and suggests a population incidence of 1 in 33, 000 to 40, 000. In the UK as a whole, 150 cases have been identified and been used to study the clinical and genetic features of NF2. The autosomal dominant inheritance of NF2 was confirmed, 49% of cases were assessed as representing new mutations, and the mutation rate was estimated to be 6.5 x 10(-6). Evidence to support a maternal gene effect was found in that age at onset was 18.17 years in 36 maternally inherited cases and 24.5 in 20 paternally inherited cases (p = 0.027). The preponderance of maternally inherited cases was also significant (p = 0.03). Data are presented which suggest that there are two types of NF2, one with later onset and bilateral vestibular schwannomas as the only usual feature, and the other with earlier onset and multiple other tumours. A considerable number of cases did not fall easily into one or other group and other factors such as maternal effect on severity and anticipation need to be considered.